7A.001 Adolescent's perception of road risk on their routes to school in Makwanpur, Nepal; a qualitative study. (14th March 2021) - Gautam, Preeti; Mytton, Julie; Pilkington, Paul; Joshi, Sunil
Abstract : Background: Busy and poor road infrastructure along routes to school poses high risk of traffic injury for children. Every child's safe and healthy journey to/from school is fundamental to achieving Sustainable Development Goal 3.6. However, there is little evidence reporting children's views about their school travel from developing countries. This study aims to understand children's perceptions of injury risks on their journey to school in Nepal. Methods: We used Photo-Elicitation Interview (PEI) methods to collect data from 14 children (12–16 years) who walk to school along the East-West Highway in Makwanpur, Nepal. The children used a camera to record parts of their journey, which they perceived as dangerous. Photographs were used as prompts during an interview afterwards. Interviews were audio-recorded, transcribed, translated and analysed thematically using NVivo. Results: Several themes were identified, categorised under environmental and behavioural factors. The children were scared to walk on narrow roadsides because of speeding vehicles. They also found crossing the road dangerous because of the lack of designated pedestrian crossings and disregard shown by drivers. Poor visibility caused by random roadside parking and trees also increased the sense of road danger. Conclusion: Children expressed multiple concerns which made the journey difficult and dangerous. Some of these issues could be addressed through improved road infrastructure, whilst others would require a change in driver's behaviour. Learning Outcomes: Children's views are often ignored in issues pertaining to their health and well-being. PEI is an engaging method that encourages children to express concerns about their safety.